Optimalisasi Peran Keluarga Guna Melawan Adiksi pada Anak - Myrna Anissaniwaty; Santi Rinjani; Yoko Jimmy Panjaitan; ED. Yunisa Mega Pasha; Andri Nurmansyah; Euis Teti Hayati (Jurnal Abdimas Kesehatan (JAK), 2023)
Addiction is often something to be feared or avoided, one of which is online games. This is also a problem or issue that arises in one of the leading private schools in the city of Bandung, Baitul Hikmah Elementary School. In the learning process, Baitul Hikmah Elementary School still has not found a more effective solution in overcoming the problem of time-consuming online game activities. The role of parents and teachers is needed in accompanying children to be able to face their obstacles or find effective ways to manage time and energy. For this reason, understanding and abilities are needed that specifically need to be purchased or directed to parents and teachers so that they are able to accompany children in handling addictive behavior. This community service activity aims to provide education and spur self-development for parents, teachers and students in preventing or reducing the negative effects of online games. Implementation of this community service activity by examining/screening gadget addiction to students at Baitul Hikmah Elementary School found 52% experienced game addiction, providing education on online game addiction behavior to children and problem solving was carried out through the zoom platform which was attended by 42 student respondents and parents. Furthermore, providing counseling as a form of handling and preventing negative impacts which are increasing as a result of playing online games which were attended by 13 parents of students, as well as triggering and triggering the achievement of all activities that have been carried out. The results of this activity have a positive impact, namely an increase in knowledge about the factors that influence online game addiction behavior after receiving education and counseling.